Training the Trainer of an International Medical Graduate - Akshith Shetty; Harleen Birgi; Ian Hall; Rahul Bhattacharya (BJPsych Open, 2025)
Aims: More than half of new recruits in the NHS are International Medical Graduates (IMGs). It is recognised that IMG need additional support, however to offer this their supervisors need to be aware of the landscape and resources to effectively support them. We developed a training for supervisors of IMGs using a mix of didactic, group work and simulation training.